Faculty Engagement in Addressing Academic Integrity Challenges - Rahimian, Matt (Canadian Perspectives on Academic Integrity, 2023)
Over the past few years, academic integrity has gained more attention in post-secondary education. New and innovative ways are devised to cheat in academia, and academic integrity practitioners and schools are actively learning about new ways of academic misconduct. Respectively, these practitioners and scholars are actively seeking ways of deterring academic misconduct and promoting integrity. Since the pandemic began, more attention has been given to academic misconduct as more such cases have been reported at several post-secondary institutions (Dubinski, 2023). Some examples of the more recent nuances in academic misconduct include using Artificial Intelligence to write essays (e.g. Coppolino, 2023; Oppenheimer, 2023), using a combination of spy glasses and smart watches to cheat during exams (e.g. Chugh, 2016; Storm, 2016), and use of social media in the service of academic misconduct (e.g. Lancaster, 2019). On the other hand, academic integrity practitioners and scholars have proposed ways to address the academic integrity challenges. Many of them have proposed ways to educate students on maintaining academic integrity and deterring misconduct cases (e.g. Gallant, 2017; Mitchell & Parnther, 2018), and some have advocated for restorative measures after misconduct cases are found (Sopcak &Hood, 2022). Yet, one of the areas that need further work, in general, is faculty engagement in academic integrity enhancement. This is the area that I will focus on in this paper. I propose using curriculum-integrated approaches, goal alignment techniques, and practice/discipline-specific approaches to increase faculty interest in engaging with academic integrity activities.